Pengaruh Kepemimpinan Kepala Sekolah dan Kompetensi Guru terhadap Kinerja Guru melalui Motivasi Guru - Siti Maesaroh; Farida Yuliaty; Dety Mulyanti (Journal on Education, 2024)
The performance of teachers plays a vital role in shaping the standards of education and the prospects of future generations. This research reveals a comprehensive analysis of the impact of School Principal leadership and teacher competence on teacher performance through teacher motivation in Kindergarten schools in the Cilengkrang Sub-District, Bandung Regency. The research methodology involves both descriptive and inferential methods, with 46 teachers participating as samples. Data were analyzed using Smart PLS4 software with path analysis. The main findings indicate that School Principal leadership significantly influences teacher performance, while teacher competence does not have a significant effect on teacher performance. Additionally, there is no significant influence between School Principal leadership and teacher competence on teacher motivation, as well as teacher motivation on teacher performance. Teacher motivation also does not act as a mediator between School Principal leadership and teacher competence on teacher performance. Furthermore, School Principal leadership, teacher competence, and teacher motivation collectively have a significant impact on teacher performance. The implications of these findings can assist in improving educational management and empowering teachers in early childhood education environments.